UZBEK PEOPLE ORAL CREATIVITY TOOLS UZBEK PEOPLE IN PEDAGOGY HELD PLACE - Abdurahimova Muhabbat Allayevna (Scholar Express Journal, 2023)
In the article people oral creativity by means of future teachers spiritual and moral education improvement, future pedagogues spiritual - moral education development social importance about recommendations given, Uzbek people oral creativity tools Uzbek people pedagogy held place about data given.
Keywords: Uzbek folklore; cultivation of thinking; national value